Y =ax² + bx +c
1) Point (0,7)
7 = a*0² +b*0 +c
c = 7
y=ax² + bx + 7
2) Point (1,4)
4=a*1² + b*1 + 7, ----> 4 = a +b + 7, ------>
a+b= - 3
3) Point (2, 5)
5=a*2² + b*2 + 7, ----> 5=4a+2b +7,---> -2=4a+2b, ---->
-1=2a + b
4)
a+b= - 3, ----> b= -3 - a (substitute in the second equation)
2a+b= -1
2a - 3 - a = -1, ----> a - 3 = -1,
a =2
5) a+b= - 3
2 + b = -3
b = -5
y=2x² - 5x + 7
Answer:
( - x, - y )
Step-by-step explanation:
The starting is always Quadrant I.
270 degrees clockwise from Quadrant I is Quadrant III.
In Quadrant III, the points will be in the form ( - x, - y ).
Answer:
[-8,8]
Step-by-step explanation:
I’ll say about 45 because one year hurt but my bones hurt one time and they did not like it
Answer: A
Step-by-step explanation:
when you substitute all the x values in the table of values from A, you get all the y values in the table